The disappearing trick : poems - Roberts, Len, 1947-2007 (Illinois poetry series., 2007)
In The Disappearing Trick, Len Roberts wrestles with the loss of loved ones--whether that loss be through death, a son moving away to college, or simply how people fade from our lives and memories. Hybrids of the narrative and lyric form, these poems are models of indirect statement that have, as Sharon Olds has said, emotional courage, powerful music, and a deep balance.? Like the light shining on a face, or a girls thigh back in a sixth-grade class, the poems often come as Proustian flashes--lasting just a second, but seeming eternal--amid an increasing darkness. _x000B_